1991
DOI: 10.7326/0003-4819-115-12-942
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Loss of Consciousness during Automatic Implantable Cardioverter-Defibrillator Shocks

Abstract: Patients with sustained ventricular tachycardia or ventricular fibrillation who receive an AICD that delivers only high-energy shock therapy are at moderate risk for experiencing loss of consciousness during AICD shocks. No clinical variables were found to be predictors of syncope. Therefore, driving and other activities that require patients to be extra vigilant should not be assumed to be safe after implantation of an AICD that delivers only high-energy shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…However, symptoms of impaired consciousness during the first appropriate ICD therapy are not unambiguously predictive for future syncope during subsequent shocks. 31,37 In a study of 125 ICD patients by Freedberg et al ., 19 the median freedom from ICD therapy for the second shock was only 22 days, with a 1-year cumulative incidence of a second appropriate shock being 79%. These were all secondary prevention ICD patients and the cumulative incidence for a second appropriate shock shows large dissimilarity when compared with the 1-year cumulative incidence of 32% observed in the secondary prevention group in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…However, symptoms of impaired consciousness during the first appropriate ICD therapy are not unambiguously predictive for future syncope during subsequent shocks. 31,37 In a study of 125 ICD patients by Freedberg et al ., 19 the median freedom from ICD therapy for the second shock was only 22 days, with a 1-year cumulative incidence of a second appropriate shock being 79%. These were all secondary prevention ICD patients and the cumulative incidence for a second appropriate shock shows large dissimilarity when compared with the 1-year cumulative incidence of 32% observed in the secondary prevention group in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Akiyama et al found that the MVC rate in a similar population was less than that in the general population (33). Unfortunately, Kou et al found there were no clinical variables, such as history of syncope, electrophysiologic findings, or age, in 180 patients who had had an AICD implanted for VT or VF, that would predict who would or who would not experience syncope or when (34).…”
Section: Cardiac Diseasementioning
confidence: 91%
“…A similar finding was described by Bansch et al [72] In this study, patients with slow VT and absence of syncope during the first ICD therapy had a low risk of developing future syncope. However, in the study of Kou et al [76], the absence of syncope during the first ICD therapy did not predict the absence of syncope during subsequent shocks.…”
Section: Risk Of Driving After Implantable Cardioverter Defibrillatormentioning
confidence: 96%